Türk sermaye piyasasında aracı kurumların piyasa yapısı ve etkinlik analizi (1999-2002 dönemi veri zarflama analizi uygulaması) - Aslantaş, Şahin (My University, 2004)
This study has two purposes. This paper firstly attempts to measure the level of concentration and competition where the brokerage firms are active in by determining the structure of the market. Second purpose is to measure the effectiveness of these operations via Data Envelope Analysis by using the trade volume of the brokerage firms realized in the Istanbul Stock Exchange (ISE) and commissions from these activities as an output. Based on this market analysis research, we can conclude that the Turkish brokerage firms face with restrictions on the entrance in and exit out of the market, the market's loaded up with so many brokerage firms, and has an oligopolistic structure with an increasing concentration and competition in Turkey. Looking at the existant market structure and its activities, this paper suggested that brokerage firms are in fact capable of maintain business and continue to exist in the market by the commissions taken from their clients for transactions. The capital, personnel and general management expenses are the main inputs that the brokerage firms use in order to carry on their activities. Therefore, the definition of effectiveness for brokerage firms is; to gain maximum amount of commission earnings along with trade volume by using minimum amount of equity capital, personnel and general management expenses. The differantiation of the operations among the clients and the portfolio trades are not included in the definition of effectiveness. According to the results of the Data Envelope Analysis done with the data of 90 brokerage firms that are uninterruptedly active in the ISE during the 1999-2002 period, many brokerage firms do not display activity fitting to the definition of effectiveness and have idle capacity due to insufficient amount of trade volume. Operative brokerage firms, on the other hand, are determined as low-scale institutions with flexible management structure along with easily changeable cost structures.

Bu çalışmanın iki amacı vardır. Bunlardan birincisi aracı kurumların faaliyet gösterdikleri piyasa yapısının tespitini yaparak, yoğunlaşma ve rekabet seviyesini ölçmek, ikincisi ise aracı kurumların İMKB hisse senetleri piyasasında gerçekleştirdikleri işlem hacmi ve bu faaliyetden elde edilen komisyon gelirlerini çıktı olarak kabul edip Veri Zarflama Analizi yöntemini kullanarak bu işlemlerin etkinliğini ölçmektir. Yapılan piyasa analizine göre Türkiye'de aracı kurum piyasasına giriş ve çıkışların kısıtlandığı, gereğinden fazla çok sayıda aracı kurumun faaliyet gösterdiği, yoğunlaşmanın ve rekabetin giderek arttığı oligopolistik bir piyasa yapısına sahip olduğu görülmüştür. Mevcut piyasa yapısı ve faaliyetleri dikkate alındığında, aracı kurumlar gerçekleştirdikleri işlem hacmi üzerinden aldıkları komisyon gelirleri ile varlıklarını sürdürmektedirler. Aracı kurumların faaliyetlerini sürdürmek için kullandıkları temel girdiler ise Sermaye, personel ve genel yönetim giderleridir. Buradan hareketle aracı kurumlar için yapılan etkinlik tanımında minimum özkaynak, personel ve genel yönetim gideri kullanarak en fazla işlem hacmi ve komisyon geliri elde etmektir. Aracı kurumlar tarafından gerçekleştirilen işlemlerin müşteri ve portföy işlemi ayrımı, yeterli bilgi olmadığından etkinlik tanımına dahil edilmemiştir. 1999-2002 yılları arasında kesintisiz faaliyet göstern 90 aracı kurum verileri kullanılarak yapılan Veri Zarflama Analizi sonuçlarına göre bir çok aracı kurumun etkinlik tanımına uygun faaliyet göstermediği, yetersiz işlem hacimleri nedeniyle atıl kapasiteye sahip oldukları, etkin olarak bulunan aracı kurumların ise maliyet yapılarını kolay değiştirebilen esnek yönetim yapısına sahip küçük ölçekte aracı kurumlar olduğu tespit edilmiştir.
Keywords: Ekonomi; Finansman ekonomisi; Sermaye Piyasası